Effect of blanching conditions on physico-chemical characteristics of cocoa pod husk - Anoraga, Satria Bhirawa; Shamsudin, Rosnah; Hamzah, Muhammad Hazwan; Sharif, Suzannah; Saputro, Arifin Dwi (Universiti Putra Malaysia, 2025)
Effective post-harvest handling and grading of cocoa fruit require a comprehensive understanding of its physical and chemical characteristics. The cocoa pod husk (CPH), a significant by-product, has potential applications due to its valuable chemical properties. The present work thus aimed to (1) characterise the physico-chemical properties of cocoa fruit and its husk, (2) develop predictive models for cocoa fruit mass based on physical parameters, and (3) optimise short-time blanching conditions to enhance the chemical quality of CPH. The methodology included measuring physical parameters (weight, dimensions, roundness, volume, surface area, and projected area), and developing predictive models for cocoa fruit mass using linear, quadratic, S-curve, and power models. Chemical analyses of CPH involved determining pH, biomass composition, total phenolic content, antioxidant activity, and dietary fibre content. Optimisation of blanching conditions was conducted using a response surface methodology with temperature and time as variables. Results indicated that a non-linear model based on projected area effectively predicted cocoa fruit mass, with the prolate spheroid volume model offering the highest accuracy. Optimal blanching conditions (79°C for 12.5 sec) yielded 36.19% crude fibre and 4.189% protein, with crude fibre content influenced by temperature, and a significant temperature-time interaction effect on protein content (p < 0.05). These findings suggested that CPH can be repurposed as a functional food ingredient rich in phenolics, antioxidants, and dietary fibre, offering practical applications for value-added agricultural waste recovery.